2012
DOI: 10.3390/molecules170911173
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Hexane Extract of Citrus aurantifolia and Anti-Mycobacterium tuberculosis Activity of Some of Its Constituents

Abstract: The main aim of this study was to isolate and characterize the active compounds from the hexane extract of the fruit peels of Citrus aurantiifolia, which showed activity against one sensitive and three monoresistant (isoniazid, streptomycin or ethambutol) strains of Mycobacterium tuberculosis H37Rv. The active extract was fractionated by column chromatography, yielding the following major compounds: 5-geranyloxypsoralen (1); 5-geranyloxy-7-methoxycoumarin (2); 5,7-dimethoxycoumarin (3); 5-methoxypsoralen (4); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 39 publications
3
43
0
3
Order By: Relevance
“…Among active ingredients contained in the lime extract are flavonoids (polyethoxylated flavones and flavanones), coumarin, and terpenoids, all of which act as antibacterials 32 . Extract prepared from peel, fruit and leaves of lime show promising antibacterial activity against some microbes belong to both gram positive bacteria ( Staphylococcus aureus, S. epidermis and E .…”
Section: Discussionmentioning
confidence: 99%
“…Among active ingredients contained in the lime extract are flavonoids (polyethoxylated flavones and flavanones), coumarin, and terpenoids, all of which act as antibacterials 32 . Extract prepared from peel, fruit and leaves of lime show promising antibacterial activity against some microbes belong to both gram positive bacteria ( Staphylococcus aureus, S. epidermis and E .…”
Section: Discussionmentioning
confidence: 99%
“…The saturated fatty acid palmitic acid exhibited higher activity against multidrug-resistant M. tuberculosis strains (MICs = 50 µg/ml) than the unsaturated fatty acids oleic acid and linoleic acid, which showed less activity (MICs = 100 µg/ml) [108].…”
Section: Citrus Speciesmentioning
confidence: 99%
“…Mexico: Sandoval-Montemayor et al . [33] reported that C. aurantifolia fruit peels consist of 44 volatile compounds, for example, dimethoxycoumarin (16%), cyclopentanedione (9%), methoxycyclohexane (8%), corylone (7%), palmitic acid (7%), dimethoxypsoralen (6%), α-terpineol (6%), and umbelliferone (5%).…”
Section: Introductionmentioning
confidence: 99%